Funcionamiento cognoscitivo en la diabetes tipo 2: una revisión. - Huerta, Karina Cerezo; Téllez, Guillermina Yáñez; Aguilar Salinas, Carlos Alberto; Mancilla Díaz, Juan Manuel (Salud Mental)
The aim of this work is to offer an updated review of the major cognitive difficulties that appear in Type 2 Diabetes Mellitus (T2DM), and its association with the patient compliance related factors proposed by the Panamerican Health Organization (PAHO), such as characteristics of patient, of the disease and of treatment. The review included electronic databases search (PubMed, Psy-cINFO and SpringerLink) from January 2000 to December 2011, predominating research from the United States, Canada, Holland, UK, Japan, Mexico and Germany. Most of the reviewed articles identified that factors which have shown to be associated with cognitive functioning in T2DM include: glycemic fluctuations, disease duration and pharmacological treatment. As for the changes that occur in the Central Nervous System (CNS), to date there is no consensus as to whether these are purely degenerative, vascular or a combination of both. Most affected cognitive abilities are: verbal memory, working memory, verbal fluency, attention, mental planning and psychomotor speed. The latter have been related with frontal, temporal and hyppo-campal structure functioning, which are also compromised on T2DM. In the cognitive aspect, it is reported that T2DM is a risk factor for developing mild cognitive impairment. Also, chronicity of this condition associated with hypertension, inadequate glycemic control, and macrovascular complications increases the odds for vascular dementia to occur. It is concluded that even though some risk factors of the cognitive deficiencies have been identified on T2DM, it is important to determine how they interact, and to what degree they affect overall cognitive performance, and specific functions in this population.